O papel constitucional do juiz na recuperação judicial - Moretti, Luciana de Souza Cavar (2022)
The main objective of this work is to analyze and investigate the relationship between the role of the judge and the judicial reorganization process, having as a goal the jurisprudential position of the Superior Court of Justice. In the first chapter, we sought to analyze and understand the relationship between constitutional law and civil law and access to justice for companies in crisis, highlighting the role of the State in situations of economic crisis and overcoming it, in order to to understand the crisis formation process, its reflexes and its differentiation between rigidity crisis, efficiency crisis, economic crisis, financial crisis and patrimonial crisis. Furthermore, an attempt was made to differentiate between recoverable and non-recoverable companies, since the preservation of viable business activity is in the public interest. In this way, we tried to study the principle of preservation of the company as a vector that seeks to continue the productive activity and that respects the social, fiscal, economic and environmental function. In the next chapter, the functions, postures and conducts that the judge must have in the conduct of the recovery process were treated, taking into account the current context of Law 11.101/2005. Thus, a brief historical analysis was carried out to understand to what extent the judge must act, guided by the guiding principles of the applicable legislation. In this way, six roles were proposed that the judge plays in the conduct of the process: the authorizing, the watchman, the mediator/conciliator, the modifier, the enforcer and the finalizer, all marked not by the action along the specific phases of the judicial reorganization process, but for the decision-making content that it utters, considering the company's situation and the interest of creditors. Finally, in the last chapter, the jurisprudence guiding and standardizing the understandings of the Superior Court of Justice was analyzed, with emphasis on the Precedents, Repetitive Appeals and Incidents of Assumption of Jurisdiction. Going all this way, it was intended to investigate the problem of the inexorability of judicial control, since it is the judge himself who is the driver of the judicial recovery process. However, it was intended, at the same time, to investigate whether such jurisdictional control is restricted only to formal aspects or if there are situations in which the judge can enter the very merits of the recovery process and, if so, to what extent. To make this dissertation viable, the hypothetical-deductive method of approach was used, in which there is theoretical research with the investigation of the premises, to prove the hypothesis, through bibliographic analysis.